2017
DOI: 10.1038/s41598-017-02644-w
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive stochastic resonance for unknown and variable input signals

Abstract: All sensors have a threshold, defined by the smallest signal amplitude that can be detected. The detection of sub-threshold signals, however, is possible by using the principle of stochastic resonance, where noise is added to the input signal so that it randomly exceeds the sensor threshold. The choice of an optimal noise level that maximizes the mutual information between sensor input and output, however, requires knowledge of the input signal, which is not available in most practical applications. Here we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 29 publications
4
72
0
5
Order By: Relevance
“…In self-adaptive signal detection systems exploiting SR, the optimum intensity of the noise is continuously adjusted so that information transmission is maximized, even if the characteristics and statistics of the input signal change (Figure 2). For this processing principle, the term adaptive SR has been coined (Mitaim & Kosko 1998Wenning & Obermayer 2003;Krauss et al, 2017).…”
Section: Stochastic Resonancementioning
confidence: 99%
“…In self-adaptive signal detection systems exploiting SR, the optimum intensity of the noise is continuously adjusted so that information transmission is maximized, even if the characteristics and statistics of the input signal change (Figure 2). For this processing principle, the term adaptive SR has been coined (Mitaim & Kosko 1998Wenning & Obermayer 2003;Krauss et al, 2017).…”
Section: Stochastic Resonancementioning
confidence: 99%
“…The term adaptive SR was coined for this processing principle [18][19][20]. In a previous study we demonstrated that the auto-correlation of the sensor output, a quantity always accessible and easy to analyze by neural networks, can be used to quantify and hence maximize information transmission even for unknown and variable input signals [21].…”
Section: Introductionmentioning
confidence: 99%
“…11,13,14,18,29,30 However, they are unavailable when the target frequency is unknown. As to this problem, some criterions are proposed such as approximate entropy, 12 MPSK index, 17 mutual information, 31 and weighted power spectrum kurtosis. 32 This study focuses on the relationship between the parameters of SFrSR and its output.…”
Section: Discussionmentioning
confidence: 99%